Facebook Use by Peruvian Physicians:Exposing Private Life to Patients - Pereyra Elías, Reneé (2014)
Facebook, a social networking service with over 100 million unique users, is widely established in many contexts around the world. A significant number of physicians have opened Facebook accounts [1, 2] , which is resulting in major ramifications for the medical profession.